Моделирование процесса выплавки стали в металлургическом производстве - Кабулова, Евгения Георгиевна; Косарева, Ирина Николаевна; Карпова, Валентина Алексеевна; Гриднева, Галина Ильинична (Национальный технический университет "Харьковский политехнический институт", 2015)
Проводится анализ особенностей моделирования процесса выплавки стали, делается вывод, что наиболее адекватным подходом к построению моделей зависимости твердости стали от еѐ химического состава являются методы статистического моделирования в комбинации с методами нечеткого логического вывода. Исследуется и разрабатывается модель зависимости распределенной по глубине твердости стали от еѐ химического состава в виде системы нечетких продукционных правил (модель Токаги-Суджено-Канга - TSK). Данная модель позволит определять прогнозные значения распределенной твердости стали как средневзвешенные выходы комплекса моделей линейной регрессии, а также устранит проблему выбора наиболее адекватной регрессионной модели.

The analysis of features of modeling the process of steelmaking, concluded that the most appropriate approach to the construction of models depending on the hardness of steel from its chemical composition are statistical modeling techniques in combination with the methods of fuzzy logic, and control of the process of steelmaking (choice of chemical composition) may be represented as either a solution of systems of nonlinear equations, or as a model of optimal choice. The study developed a model depending on the depth distribution of the hardness of steel from its chemical composition in the form of fuzzy production rules (model Tokagi-Sugeno-Kang TSK), which will determine the predictive value of the distribution of hardness of steel as the weighted average yields of complex linear regression models and eliminate the problem of choice most appropriate regression model. This model TSK planned to further explore its value as part of the requirements for the accuracy of determining the distribution of the hardness of steel, set individual customer specifications on smelted products.
Optimal algorithms for process control steelmaking in metallurgical production
Keywords: металлургические предприятия; прогнозирование твердости стали; статистическое моделирование; нечеткий логический вывод; нечеткие продукционные правила; forecasting the hardness of steel; fuzzy production rules